CSR reports in the 21st century: Has time of stories, fablesand legends elapsed? - Antczak, Zbigniew (Research Papers of Wrocław University of Economics, 2018)
The purpose of the research was confronting corporate declarations in the CSRarea with their numerous unethical practices for which information was found in variousmedia. The study is unique because there are no critical analyzes based on empirical studies.The following research methods were used, among others: content analysis, network analysis,archival analysis, case study, targeted selection, random selection, evaluation, documentresearch, monitoring, observation, triangulation and expert selection. Conclusions fromthe results of research: globalization of conducting business, at breaking the relationshipbetween the owner (owners, shareholders), managers and employees (contractors, as part ofoutsourcing: subcontractors) de facto led to a total lack of accountability to society (and/orthe state). In the axiological sphere, it found expression in a radical transformation of valuesystems and focusing on profit, and perception of greed as virtue
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2018; Nr 520; s. 9-21
Keywords: CSR reports; ethics; corporate social responsibility; crisis of values; axiology; raporty CSR; etyka; społeczna odpowiedzialność biznesu; kryzys wartości; aksjologia